Les indicateurs de biodiversité marine et côtière : état des lieux institutionnel - Levrel Harold; Julia Fossat; Dominique Pelletier (VertigO)
2010 is the year of biodiversity. Since the 90’s, many biodiversity indicators have been developed to monitor biodiversity trends. This paper proposes a review of the marine biodiversity indicators which are included into international and regional conventions as well as those which are in the regulation and strategic acts at a French and European scale. At the same time, we listed the conceptual frameworks used from which it is possible to interpret these biodiversity indicators.This work enables us to underline that most indicators are not related to a specific conceptual framework and rather associated to broad topics, and that most indicators are less focused on the component of biodiversity itself than on the anthropogenic pressures and the ecosystems services that biodiversity delivers to human society. Among the components of the biodiversity indicators are mainly focused on rare species and habitats. A great number of these indicators are not used, nor implemented.